School Culture, Structure and Practices as Correlates of Students’ Self- Efficacy and Achievement in Senior Secondary School Mathematics in Oyo State, Nigeria (2014)
Stakeholders in education are concerned about general poor performance in mathematics and the low level of mathematics self- efficacy displayed by students in Oyo state. Studies from some other climes showed that school culture, structure and practices are predictors of achievement and self-efficacy in mathematics. Available studies in Oyo State used selfefficacy to predict achievement in mathematics. There seems to be dearth of study on how school culture, structure and practices predict self-efficacy and achievements in mathematics. This study, therefore, examined the extent to which school culture, structure and practices determined students‟ self-efficacy and achievement in mathematics in senior secondary schools in Oyo State. Survey design was used while multistage sampling technique was adopted. Five local government areas (LGA) were randomly selected from Oyo state and the secondary schools in the LGA were stratified into high performing schools (HPS) and low performing schools (LPS). Schools where 40% of the students recorded credit pass in mathematics at the senior secondary certificate examinations in the last five years were classified as HPS, while others were regarded as LPS. From each LGA, 4 schools were randomly selected from each stratum. Also, 30 students and 4 teachers of mathematics were randomly and purposively selected respectively from each school. In all, 40 schools, 1,200 students and 160 teachers participated. Five instruments were validated using 50 students and 30 teachers. They were: the School Culture Scale (α = 0.81), School Structure Scale (α = 0.75), the School Practices Questionnaire (α = 0.81), the Mathematics Self-Efficacy Scale (α = 0.78) and the Mathematics Achievement Test (α = 0.80). Mean, standard deviation, t-test and multiple regression were used to analyse the data at p< 0.05. One hundred male and 60 female teachers had mean age= ±40.86; SD=9.56, while 500 male and 700 female students had mean age= ±15.56; SD=.92 in the study. Mean scores of HPS and LPS students‟ achievement in mathematics were ( =26.78; SD =4.52 and ( =14.95; SD =3.35) respectively. Self-efficacy and achievement in mathematics of students in HPS were significantly better ( =134.22; SD =6.02) than those of LPS ( =19.19; SD =11.65);( t= 18.80, df =158) (achievement) and t= 24.58 (self-efficacy). A significant relationship existed between the school culture, structure and practices, and achievement in mathematics (HPS: R = .389, F (3, 76) = 4.520 and LPS: R= .652, F (3, 76) =18.711) and selfefficacy (LPS: R=.304, F (3, 76) = 7.981) respectively. In HPS, only school structure significantly predicted achievement (β=.435), while in LPS, school culture (β=.471) and school structure (β=.244) significantly predicted achievement. None of culture, structure and practices significantly predicted self-efficacy in HPS, while school culture (β=.330) and school structure (β=.266) significantly predicted self-efficacy in LPS. Students in high performing schools are efficacious and better academically than those in low performing schools in mathematics. It is only school structure that predicted achievement in high performing schools while school culture and structure predicted achievement in low performing schools. Good school culture, structure and practices should be encouraged in schools